Qualitative assessment of the suitability of the Dysphagia Symptom Questionnaire to monitor dysphagia in children aged 7-10 years with eosinophilic esophagitis - Robin M. Pokrzywinski; Bridgett Goodwin; Evan S. Dellon; Ellyn Kodroff; Anne Brooks; Adam Bailey; James Williams; Nirav K. Desai (SpringerOpen, 2023)
Abstract Background The Dysphagia Symptom Questionnaire (DSQ) is a patient-reported outcome measure that assesses the frequency and severity of dysphagia in patients with eosinophilic esophagitis (EoE); however, it has only been validated for use in patients with EoE aged 11-40 years. This study examined the content validity of the DSQ and its usability on an electronic handheld device in children aged 7-10 years with EoE. Methods In this qualitative, observational cohort study, participants were recruited to partake in two rounds of interviews. During visit 1, a cognitive interview examined EoE-associated concepts and the appropriateness of the DSQ for assessing dysphagia. Participants completed the DSQ daily for 2 weeks, and DSQ scores were calculated. After 2 weeks, a second interview assessed the usability of the DSQ on the electronic device and the burden associated with completing it daily. Results Overall, 16 participants were included (aged 7-8 years: n = 8; aged 9-10 years: n = 8); most were male (75%) and white (81%), and the mean (standard deviation [SD]) age was 8.4 (1.3) years. The most commonly reported EoE-associated concept was 'trouble with swallowing' (63% [10/16]). Most participants reported that the questions were 'easy to complete' and 'relevant to someone with EoE and dysphagia'. Overall, participants reported understanding the questions and associated responses; however, further probing demonstrated inconsistent comprehension. Key challenging concepts included 'solid food', 'trouble swallowing', 'vomit', and 'relief'; some participants also reported difficulty differentiating between pain levels (31% [4/13]). Most caregivers reported that their child had experienced dysphagia (94% [15/16]); however, mean (SD) DSQ scores over the study period were low (7.3 [7.4]), suggesting infrequent and mild dysphagia, or a lack of comprehension of the questions. Most participants reported that completing the DSQ on the electronic device was easy (93% [14/15]) and they would be willing to complete it for longer than 2 weeks (73% [11/15]). Conclusions Difficulties with comprehension and comprehensiveness suggest that the DSQ may not be sufficiently comprehensive for use in all patients in this population, and wording/phrasing changes are required before use in a clinical trial setting.